Estradiol level on day two and day of trigger: A potential predictor of the invitro fertilization success - Ahmed Mohammed, Alaa; Khudhur Mawlood, Chiman (Zanco Journal of Medical Sciences (ZJMS), 2024)
Background and objective: Infertility is defined as not getting pregnant after 12 months of unprotected sex for women under 35 or 6 months for those over 35. Ten to fifteen percent of couples struggle to conceive. All cases of infertility are evaluated; however, evaluations should be conducted sooner if there is a male factor or if the female has endometriosis, tubal illness, oligomenorrhea, or amenorrhea. Investigation includes an assessment of ovulatory function, ovarian reserve, uterinecavity, tubalpatency, and a semen analysis, diagnostic laparoscopy, hormone levels estradiol, the number of ovarian antral follicles have role in successful pregnancy in IVF cycles. It is generally known that a particular quantity of estradiol per follicle is necessary for pregnancy to occur. The purpose of this study was to evaluate the effects of IVF on the normal level of E2 in follicular day (12.5-166 pg/ml) and ovulation day (85.5-498 pg/ml) in relation to the estradiol level. Methods: Because it depended on a few indications (questionnaire), the retrospective study of 50 infertile women at the YAD infertility center in Erbil, Kurdistan Region, Iraq, was analyzed. Results: In this research the median age was 33 years, and their mean age (SD) was 32.6 (5.9) years. Their average body mass index was ≥ 30 at 28%, although their rate was 34%.Over 38% of women have no history of pregnancy, which is also more common in multigravidas than in primigravidae. In contrast, 23% of nulliparous women are infertile, and 46% of infertile women are nulliparous compared to primiparous and multiparous women. While the success rate was highest for the type of oocyte (M II) (89.7%) compared to 65% for the other types, the mean estradiol level on day 2 of the cycle was 46.9%, and the mean estradiol level on the day of HCG administration was also higher among women with successful biochemical pregnancies than those with failed pregnancies. Conclusion: The estradiol 2nd day of cycle and the trigger day was found to have influence on IVF success.